2022
DOI: 10.31234/osf.io/q4d9g
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Equilibrium Causal Models: Connecting Dynamical Systems Modeling and Cross-Sectional Data Analysis

Abstract: Many psychological phenomena can be understood as systems of causally connected components that evolve over time within an individual. In current empirical practice, researchers frequently study these systems by fitting statistical models to data collected at a single moment in time, that is, cross-sectional data. This poses a central question: Can cross-sectional data analysis ever yield causal insights into systems that evolve over time, and if so, under what conditions? In this paper, we address this questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…It is not clear what a cross sectional bi-directional effect means without further study, perhaps contemporaneous change in A causes change in B while change in B causes change in A. Alternatively, these causal effects may have played out in the past shaping the current distribution of the data, but the variables may no long be amenable to change. A paper explores the limits of what can be learned about temporally unfolding processes from cross-sectional data (Ryan & Dablander, 2022) used the backshift algorithm (Rothenhäusler et al, 2015), which has clear similarities to the multi-group SEM model that we outlined above. Another apparent sources of indeterminacy that might arise the presences of interindividual differences in causal processes, which would require further adaptation of the models and put additional requirement on the data (e.g., the requirement of time-series data).…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear what a cross sectional bi-directional effect means without further study, perhaps contemporaneous change in A causes change in B while change in B causes change in A. Alternatively, these causal effects may have played out in the past shaping the current distribution of the data, but the variables may no long be amenable to change. A paper explores the limits of what can be learned about temporally unfolding processes from cross-sectional data (Ryan & Dablander, 2022) used the backshift algorithm (Rothenhäusler et al, 2015), which has clear similarities to the multi-group SEM model that we outlined above. Another apparent sources of indeterminacy that might arise the presences of interindividual differences in causal processes, which would require further adaptation of the models and put additional requirement on the data (e.g., the requirement of time-series data).…”
Section: Discussionmentioning
confidence: 99%
“…Conceptually, a number of researchers in the causal modeling literature have shown that, under certain conditions, cyclic causal models fit to cross-sectional data may be interpreted as reflecting causal relations between equilibriums or resting states of a dynamic system (Iwasaki & Simon, 1994;Dash, 2005;Strotz & Wold, 1960;Spirtes, 1995;Mooij et al, 2013;Weinberger, 2021;Bongers et al, 2022). From this perspective, cyclic causal relations should be interpreted as a kind of coarse-grained or time-averaged representation of (reciprocal) causal re-lations between processes that evolve over time; for a detailed treatment of cyclic equilibrium causal models in the context of psychological modeling, we refer readers to Ryan and Dablander (2022).…”
Section: Introductionmentioning
confidence: 99%